Forensic characteristics and phylogenetic analysis of both Y-STR and Y-SNP in the Li and Han ethnic groups from Hainan Island of China. (March 2019) - Song, Mengyuan; Wang, Zheng; Zhang, Yaqing; Zhao, Chenxi; Lang, Min; Xie, Mingkun; Qian, Xiaoqin; Wang, Mengge; Hou, Yiping
Highlights: A dearth of genetic diversity in Hainan Li was observed in contrast with Hainan Han ethnic group. There was little gene flow between the Li and Han, as well as other ethnic groups in Hainan island. Founder effect existed in Hainan Li ethnic group. Our high-resolution panel performed well in population genetic studies. Abstract: Hainan Island is the southernmost and smallest Chinese province, isolated from the mainland. The Li and Han ethnic groups account for over 98% of the population on the island. However, the Li ethnic group is an indigenous community of Hainan Island, with great differences in culture, language and origin with respect to the Han, the largest ethnic group. Here, we studied these two ethnic groups from the perspective of the Y-chromosome single nucleotide polymorphisms (Y-SNPs) and short tandem repeats (Y-STRs) to unravel their forensic and phylogenetic characteristics. A total of 302 unrelated male samples from the Li and Han ethnic groups in Hainan Island were genotyped by a combination of three separate typing systems (next-generation sequencing and pyrosequencing for the Y-SNPs and capillary electrophoresis for the Y-STRs), a previously developed high-resolution panel containing 141 Y-SNPs and 27 Y-STRs. The haplotype diversity of the Li ethnic group reached 0.9997, and 49 terminal haplogroups were observed in the Li and Han ethnic groups. Haplogroup O1b1a1a1a1a1b-CTS5854 was the most predominant haplogroup, including 44.12% of Li individuals. Median-joining trees showed little gene flow between the Li and Han individuals, as well as between the Li and other ethnic groups in Hainan Island. Our results indicated that 1) in contrast with the Han ethnic group, a low degree of genetic diversity was observed in the Li ethnic group; 2) there was limited gene flow between the Li and Han ethnic groups; and 3) founder effect was identified in the Li ethnic group in Hainan Island.